Insect galectin stimulates the human CD4+ T cell proliferation by regulating inflammation (T cell and monocyte) through Th2 immune response. (February 2023) - Bhuvaragavan, Sreeramulu; Sruthi, Kannan; Nivetha, Ramanathan; Ramaraj, Paulchamy; Hilda, Karuppiah; Meenakumari, Mani; Janarthanan, Sundaram
Abstract: In this study, the galectin (OrGal) was purified from the grub of rhinoceros beetle ( Oryctes rhinoceros ) (Coleoptera: Scarabaeidae) using lactose-affinity chromatography and its molecular mass was determined as 191 kDa. The OrGal binds lactose, galactose and BSM. It is a heterotrimer whose IEF were ∼5–5.5 (50 kDa), 7 (75 kDa) and 8 (95 kDa). The OrGal was glycine-rich and showed peptide-homology to galectin and mitogenic lectin. From the isolated human PBMC, CD4 + T and CD19 + B cells were sorted and confirmed with CD markers. The OrGal was mitogenic to T-cells but not B cells (24 h and 48 h), and this activity was repressed by lactose. Expression of inflammatory mediators showed that OrGal upregulated IL-2 and IL-4, and downregulated IFN-γ, IL-6 and GM-CSF in LPS-primed-T-cells. In the LPS-primed-monocytes, OrGal downregulated NF-κB, TNF-α, IL-1β, IL-6, IL-12 and NO. The de novo transcriptomics identified transcripts (PB 3585.1 & PB 3817.1) showing identity to Coleopteran galectin-4, − 6, − 8 and − 9, in which galectin-8 & − 4 showed high similarities. Mass spectrometry sequences of OrGal and its subunit exhibited a considerable identity to PB 3585.1 (galectin-8) & PB 3817.1 (galectin-4). The in silico models of above two transcripts interacted with lactose and galactose. Graphical Abstract: ga1 Highlights: Purification and characterization of OrGal from the grub of Oryctes rhinoceros. Potent human T cell mitogenicity (not B cell) was exhibited by the OrGal. Th2-type inflammatory response was elicited by the OrGal in T cells and monocytes. OrGal was composed of Galectin- 4 and −8 transcripts to render the function.